RIII S/J (H-2r). An inbred mouse strain with a massive deletion of T cell receptor V beta genes (The Rockefeller University Press, 1989)
We have identified an inbred strain of mouse, RIII S/J (H-2r), that has the largest known deletion of the TCR V beta genes by screening with mAb and TCR V beta specific probes. Upon screening of PBL with mAb F23.1, which is specific for V beta 8 TCR, RIII S/J was found to be negative. On further screening with mAb KJ 23a, which is specific for V beta 17a TCR, RIII S/J was completely negative. We next tested RIII S/J with mAb 44-22-1, which is specific for V beta 6 TCR, and found it also to be negative. The (B10 X RIII)F1 mice showed a 50% expression of V beta 6 gene, indicating a genomic rather than a clonal deletion. mAb KJ25, detecting V beta 3, was positive in RIII S/J, denoting the downstream boundary for the deletion. Southern blot analysis of liver DNA using TCR V beta-specific probes confirmed the deletion of V beta 8 gene subfamily and V beta 5 gene subfamily, along with V beta 9, V beta 11, V beta 12, and V beta 13 genes similar to the known TCR V beta deletion mutants (SWR, SJL, C57L, and C57Br). In addition, RIII S/J is missing V beta 6, V beta 15, and V beta 17 genes. Our mapping of the deletion indicates that RIII S/J has lost approximately 130 kb of V beta chromosome and with it 13 V beta genes out of the known 21 V beta genes of the TCR. The deletion is marked by the presence of V beta 10 gene upstream and V beta 3 gene downstream.